Зимостійкість дерев’янистих ліан в умовах м. Києва - Bagatska, O.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
In the article the results of studying the winter resistance of woody lianes in condition of Kyiv are described. The dependense between duration of grow of shoots and period of vegetation and winter resistance of plants is established. The conclusions about stable of 16 species of woody lianes to unfavorable factors of winter period are maked.